One Health/EcoHealth capacity building programs in South and South East Asia: a mixed method rapid systematic review - Pranab Chatterjee; Abhimanyu Singh Chauhan; Jessy Joseph; Manish Kakkar (BMC, 2017)
Abstract Background Although One Health (OH) or EcoHealth (EH) have been acknowledged to provide comprehensive and holistic approaches to study complex problems, like zoonoses and emerging infectious diseases, there remains multiple challenges in implementing them in a problem-solving paradigm. One of the most commonly encountered barriers, especially in low- and middle-income countries, is limited capacity to undertake OH/EH inquiries. A rapid review was undertaken to conduct a situation analysis of the existing OH/EH capacity building programs, with a focused analysis of those programs with extensive OH engagement, to help map the current efforts in this area. Methods A listing of the OH/EH projects/initiatives implemented in South Asia (SA) and South East Asia (SEA) was done, followed by analysis of documents related to the projects, available from peer-reviewed or grey literature sources. Quantitative data was extracted using a data extraction format, and a free listing of qualitative themes was undertaken. Results In SEA, 13 unique OH/EH projects, with 37 capacity building programs, were identified. In contrast, in SA, the numbers were 8 and 11 respectively. In SA, programs were oriented to develop careers in program management, whereas, in SEA, the emphasis was on research. Two thirds of the programs in SEA had extensive OH engagement, whereas only one third of those in SA did. The target for the SEA programs was wider, including a population more representative of OH stakes. SEA program themes reveal utilization of multiple approaches, usually in shorter terms, and are growing towards integration with the traditional curricula. Such convergence of themes was lacking in SA programs. In both regions, the programs were driven by external donor agencies, with minimal local buy-in. Conclusions There is limited investment in research capacity building in both SA and SEA. The situation appears to be more stark in SA, whilst SEA has been able to use the systematic investment and support to develop the OH/EH agenda and strategize capacity building in the core competencies. In order to effectively address the disease emergence hotspots in these regions, there needs to be strategic funding decisions targeting capacity building in the core OH/EH competencies especially related to transdisciplinarity, systems thinking, and adaptive management.